An Analysis of Running Event Consumer Behaviors - Thomas Aicher; Jason Simmons; Alicia Cintron (Journal of Applied Sports Management, 2018)
The purpose of this study was to examine the motives, constraints, and event selection factors affecting consumers’ decisions to participate in running events, specifically for a running festival in the Midwest United States. In partnership with a large running festival in the Midwest United States, data were collected via an online questionnaire. In total, 1,650 individuals completed a portion of the survey with 1,235 completing the additional questions for this investigation yielding a 74% completion rate. Based on the results of this study, runners’ autonomous motivation was significantly greater among those who participated in more events or longer distances during the festival. Similarly, runners with greater participation levels also perceived fewer internal constraints compared to runners who with lower participation levels. Subscribe to JASM
Keywords: Running; Motivation; Constraints; Event Selection